Coupling of SPT and 3D full waveform inversion for deep site characterization. Issue 136 (September 2020) - Mirzanejad, Majid; Tran, Khiem T.; McVay, Michael; Horhota, David; Wasman, Scott J.
Abstract: Detailed information of soil/rock variability and properties for the entire volume of supporting materials is crucial for the successful design and construction of deep foundations. Traditional invasive testing methods such as the standard penetration test (SPT) and the cone penetrometer test (CPT) only sample a small volume of soil/rock properties near the device's tip. Surface-based seismic methods can provide overall subsurface conditions but are limited to shallow depths due to the dominancy of surface waves. To address this issue, we present a novel SPT-seismic testing method for deep site characterization. Seismic wavefields generated by SPT blows at various depths are recorded by a 2D grid of geophones on the ground surface, and analyzed by a 3D full-waveform inversion (3D FWI) to extract subsurface material properties. Unlike surface-based wavefields dominated by surface waves propagating near the ground surface, the SPT-seismic wavefields are rich in body waves propagating from great depths that allow extracting detailed material properties at depths. The method is tested on in-depth source synthetic data and SPT-source field data. The results of the synthetic experiment indicate that the method successfully images soil layering with a buried anomaly. Field experiment results provide new insights into its utility as a viable geophysical tool for deep site characterization. 3D subsurface S-wave and P-wave velocities within 9 m around the SPT boring are well characterized, including two deep voids at 14–18 m depth. Comparison with the surface-based 3D FWI method proves the superiority of the presented method in imaging deep structures. S-wave velocity values of the final inverted result are also compared with SPT N-values and a good overall agreement over the whole depth is observed. Highlights: A novel SPT-seismic testing method is presented for deep site characterization. Seismic waves generated by SPT blows at depths are analyzed by a 3D FWI to extract material properties. In-depth source seismic data of rich body waves provide higher characterized resolution with depth. Materials outside a SPT boring are well characterized, including identification of two deep voids.